Adjunctive Vaginal Probiotic Therapy for Preterm Premature Rupture of Membranes: A Systematic Review and Meta-Analysis of Latency Period, Maternal Infection, and Neonatal Morbidity - Vani Ardiani; Donel S; Maya Savira; Zulmaeta (HM Publisher, 2026)
Background: Preterm premature rupture of membranes (PPROM) significantly drives preterm birth rates and consequent neonatal morbidity and mortality. While standard antibiotic therapy aims to prolong pregnancy latency, it concurrently disrupts the protective vaginal microbiota. Adjunctive vaginal probiotics have been investigated as a means to restore beneficial flora, potentially mitigating ascending infection and improving perinatal outcomes. This study systematically synthesized the current randomized trial evidence regarding this adjunctive therapeutic strategy. Methods: We performed a systematic review and meta-analysis following PRISMA guidelines. PubMed, EMBASE, and CENTRAL databases were searched (2014–October 2025) for randomized controlled trials (RCTs) comparing adjunctive vaginal probiotics plus antibiotics versus antibiotics (alone or with placebo) in singleton pregnancies complicated by PPROM between 24+0 and 34+0 weeks’ gestation. Primary outcomes included the latency period (days) and maternal chorioamnionitis or infectious morbidity. Key secondary outcomes were neonatal intensive care unit (NICU) admission, neonatal sepsis, and neonatal mortality. Data were pooled using a random-effects model, calculating Mean Differences (MD) or Risk Ratios (RR) with 95% Confidence Intervals (CI). Risk of bias was assessed using the Cochrane RoB 2 tool. Results: Three RCTs, encompassing 330 participants, met the inclusion criteria. Significant methodological limitations, including high risk of bias and critical baseline confounding by gestational age in the largest trial, were identified across the included studies. A sensitivity analysis addressing high heterogeneity (I²=98%) for latency (excluding one retrospective study; n=290) indicated a modest but statistically significant prolongation associated with probiotics (MD 2.98 days; 95% CI 1.80–4.16; p<0.0001; I²=0%). Probiotic use was linked to a significantly lower risk of maternal infection (RR 0.43; 95% CI 0.24–0.77; p=0.005; I²=0%; n=270). Statistically significant reductions were also observed for NICU admission (RR 0.59; 95% CI 0.46–0.75; p<0.0001; I²=55%; n=330) and neonatal mortality (RR 0.38; 95% CI 0.18–0.81; p=0.01; I²=0%; n=270), although these estimates are likely inflated due to baseline confounding. Conclusion: This meta-analysis suggests adjunctive vaginal probiotics may offer benefits in PPROM management by modestly prolonging latency and significantly reducing maternal infectious morbidity. While substantial reductions in NICU admission and neonatal mortality were observed, these findings must be interpreted with extreme caution due to the limited quantity and low quality of the primary evidence, particularly the high risk of bias and confounding. Definitive conclusions cannot be drawn, and routine clinical adoption is not supported by current evidence. High-quality, large-scale RCTs are imperative.